2011
DOI: 10.1128/mcb.05269-11
|View full text |Cite
|
Sign up to set email alerts
|

PINCH Proteins Regulate Cardiac Contractility by Modulating Integrin-Linked Kinase-Protein Kinase B Signaling

Abstract: Integrin-linked kinase (ILK) is an essential component of the cardiac mechanical stretch sensor and is bound in a protein complex with parvin and PINCH proteins, the so-called ILK-PINCH-parvin (IPP) complex. We have recently shown that inactivation of ILK or ␤-parvin activity leads to heart failure in zebrafish via reduced protein kinase B (PKB/Akt) activation. Here, we show that PINCH proteins localize at sarcomeric Z disks and costameres in the zebrafish heart and skeletal muscle. To investigate the in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…In agreement with data from mammalian cell culture and in zebrafish, we show that loss of PINCH affects ILK protein levels and vice versa, indicating that this is an evolutionarily conserved characteristic of proteins in this adhesion complex (Fukuda et al, 2003;Stanchi et al, 2009;Meder et al, 2011). Contrary to these data, a recent publication has claimed that ILK stabilizes PINCH, but that PINCH does not stabilize ILK, basing this conclusion on qualitative immunofluorescence images, where consistent with other published data ILK localization is preserved in a stck null mutant (Clark et al, 2003;Zervas et al, 2011).…”
Section: Contributions Of Pinch Ilk and Rsu-1 To Adhesion Complex Stsupporting
confidence: 90%
See 4 more Smart Citations
“…In agreement with data from mammalian cell culture and in zebrafish, we show that loss of PINCH affects ILK protein levels and vice versa, indicating that this is an evolutionarily conserved characteristic of proteins in this adhesion complex (Fukuda et al, 2003;Stanchi et al, 2009;Meder et al, 2011). Contrary to these data, a recent publication has claimed that ILK stabilizes PINCH, but that PINCH does not stabilize ILK, basing this conclusion on qualitative immunofluorescence images, where consistent with other published data ILK localization is preserved in a stck null mutant (Clark et al, 2003;Zervas et al, 2011).…”
Section: Contributions Of Pinch Ilk and Rsu-1 To Adhesion Complex Stsupporting
confidence: 90%
“…However, we demonstrate that the reduction in ILK that is associated with stck null mutants is comparable to the reduction in ILK observed in ics mutants, which display no deficits in muscle adhesion or viability. Furthermore, a recent study in zebrafish has shown that overexpresion of ILK in a PINCH morphant does not rescue the defects caused by loss of PINCH (Meder et al, 2011). Taken together, the phenotypes associated with loss of PINCH function cannot be fully attributed to a coordinate loss of ILK.…”
Section: Contributions Of Pinch Ilk and Rsu-1 To Adhesion Complex Stmentioning
confidence: 93%
See 3 more Smart Citations